Reconfigurable Exomuscle System Employing Parameter Tuning to Assist Hip Flexion or Ankle Plantarflexion - Ma, Zhuo; Wang, Yingxue; Zhang, Tianyu; Liu, Jianbin (IEEE/ASME transactions on mechatronics, 2025)
Pneumatic artificial muscles are extensively employed in soft wearable robotic systems to assist the movements of human joints. Nevertheless, conventional pneumatic artificial muscles make it difficult to change their configuration to adapt to different human joints. Moreover, a mismatching of assistive parameters and human motions causes poor adaptability or limited assistive performance. This study introduces a reconfigurable exomuscle system that employs the best evaluated parameters to assist hip flexion or ankle plantarflexion during walking. A set of the best evaluated parameters is determined from nine conditions with the objective of minimizing muscle activation in treadmill walking trials. Nine conditions represent different assistance timings of the exomuscle contraction and extension, which are triggered by foot plantar pressure. The system's configuration can be altered from a series mode to a parallel mode within 7 mins. Assistive performance is validated through human subject testing of ten participants in both indoor and outdoor environments. The average reduction in metabolic cost for hip flexion assistance is 9.99%, whereas the average decrease for ankle plantarflexion assistance is 7.91% in treadmill walking. Results of an outdoor environment test indicate that metabolic costs can be reduced. The system offers an alternative method to facilitate the application of reconfigurable portable devices in real-world situations.